Belajar dari Kemenangan Jepang pada Perang Tsushima: Pembangunan Kekuatan Militer Melalui Industri Strategis - Dede Rusdiana; Amarulla Octavian; Yusuf Ali; Suryono Thamrin; Aris Sarjito (Jurnal Sejarah Citra Lekha, 2021)
The various wars that have been passed have had implications for the development of Japanese combat conditions. One of the wars that sparked the rise of Japanese combat technology was the Tsushima War of 1905, marked by the use of new weaponry such as torpedoes and telegraphs. Japan's victory in the Tsushima War has proven that Japan has advanced weapons technology and has proven to be able to compete with Russia. This study provides a very important lesson and can be a reflection for Indonesia in the development of a naval military force. By using historical methods and defense economic theory approaches, this study discusses efforts to increase the strength of the main weapon system of the Japanese special navy. The results of the study show that the efforts made by Japan put a lot of emphasis on the strategy of developing the defense industry. The rise of the defense industry has become an integral part of military power building. In that context, Japan does not only involve the military, but also develops human resource capacity and increases research in the field of technology. The existence of good cooperation between the government, industry players, and academia is also the main pillar in the effort to build a naval military force.